DAKWAH DAN POLITIK ANALISIS TEKNIK MARKETING - Andries Kango (Jurnal Dakwah Tabligh, 2015)
Growing climate of democracy in Indonesia since the reform era has opened up opportunities for the various political parties to evolve. Political practice in Indonesia alone has grown so rapidly with applications utilizing various management disciplines such as marketing. Examples of the most obvious application of marketing in Indonesia is positioning in political campaigns. Given the diversity of the people of Indonesia, the positioning of a candidate or a political party should be done differently for each different segments of society. Relationship marketing and the media is very urgent, because the mass media is the type of media addressed to a number of audiences dispersed, heterogeneous and anonymous so that the same message can be received simultaneously and immediately.